Transformasi Sistem Ekonomi Pada Era Digital 4.0 Dalam Kajian Sosiologi - Muhammad Kamil Jafar (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Manado, 2023)
This study aims to examine and provide an overview of the transformation of the economic system in the digital era using a sociological approach. The research method used is a qualitative description. Current techniques and methods that have been documented by the authors in the literature, journals, papers, and other published sources have been surveyed and identified. The qualitative method was chosen because it is the most suitable approach for exploring and understanding phenomena and answering the questions that arise. The results of the research show a picture of the new world in the economic order, transformation in the digital era and the impact it has on human life.